What if something happens tonight? A qualitative study of primary care physicians' perspectives on an alternative to hospital admittance - Vivian Nystrøm; Hilde Lurås; Patrik Midlöv; Ann-Chatrin Linqvist Leonardsen (BMC, 2021)
Abstract Background Due to demographic changes, hospital emergency departments in many countries are overcrowded. Internationally, several primary healthcare models have been introduced as alternatives to hospitalisation. In Norway, municipal acute wards (MAWs) have been implemented as primary care wards that provide observation and medical treatment for 24 h. The intention is to replace hospitalisation for patients who require acute admission but not specialist healthcare services. The aim of this study was to explore primary care physicians' (PCPs') perspectives on admission to a MAW as an alternative to hospitalisation. Methods The study had a qualitative design, including interviews with 21 PCPs in a county in southeastern Norway. Data were analysed with a thematic approach. Results The PCPs described uncertainty when referring patients to the MAW because of the fewer diagnostic opportunities there than in the hospital. Admission of patients to the MAW was assumed to be unsafe for both PCPs, MAW nurses and physicians. The PCPs assumed that medical competence was lower at the MAW than in the hospital, which led to scepticism about whether their tentative diagnoses would be reconsidered if needed and whether a deterioration of the patients' condition would be detected. When referring patients to a MAW, the PCPs experienced disagreements with MAW personnel about the suitability of the patient. The PCPs emphasised the importance of patients' and relatives' participation in decisions about the level of treatment. Nevertheless, such participation was not always possible, especially when patients' wishes conflicted with what PCPs considered professionally sound. Conclusions The PCPs reported concerns regarding the use of MAWs as an alternative to hospitalisation. These concerns were related to fewer diagnostic opportunities, lower medical expertise throughout the day, uncertainty about the selection of patients and challenges with user participation. Consequently, these concerns had an impact on how the PCPs utilised MAW services.